Community-based health insurance dropout rate and its' associated factors among households in Seyo District, Kellem Wollega Zone, Oromia, Ethiopia: community-based cross-sectional study - Tafasa, Segni Mulugeta; Etana, Yonas; Keno, Firezer Belay; Fikadu, Worku; Seyoum, Dejene (Frontiers in Public Health, 2025)
BackgroundDespite an initial surge in enrollment in the Community-Based Health Insurance (CBHI) scheme, maintaining the membership remains a significant challenge in Ethiopia, particularly in the study area. High dropout rates jeopardize the program's effectiveness and long-term sustainability. Therefore, this study aimed to assess the CBHI dropout rate and its associated factors among households in Seyo District, Kellem Wollega, Ethiopia.MethodsA community-based cross-sectional study was conducted among 551 randomly selected households from eight kebeles in the Seyo district. This study employed a multistage sampling technique and took place from 1 August to 30 September 2023. Data were collected using pretested and structured questionnaires. The collected data were coded, entered into Epi Info (version 7), and analyzed using Statistical Package for the Social Sciences (SPSS version 25). Descriptive statistics were computed for key variables. Bi-variable and multivariable logistic regression analyses were performed to identify factors associated with CBHI dropout. Adjusted odds ratios (AORs) with 95% confidence intervals (CIs) were calculated to assess the strength of these associations. A p-value of < 0.05 was considered statistically significant. The results are presented as tables and graphs.ResultsA total of 546 households participated in the study, yielding a response rate of 99.1%. The overall CBHI dropout rate was 36.1% (95% CI, 32–40%). Factors significantly associated with the CBHI dropout rate included family size (AOR = 1.94, 95% CI: 1.18–3.19), age ≥51 years (AOR = 0.39, 95% CI: 0.18–0.86), being unable to read and write (AOR = 5.58, 95% CI: 2.88–10.8), being able to read and write (AOR = 3.59, 95% CI: 1.76–7.33), attending primary education (AOR = 2.45, 95% CI: 1.25–4.81), being a paying member (AOR = 2.52, 95% CI: 1.31–4.86), no history of chronic illness in the family (AOR = 1.75, 95% CI: 1.09–2.8), leaving health facilities without receiving treatment (AOR = 3.9, 95% CI: 2.29–6.57), and insufficient or unavailable laboratory services (AOR = 1.95, 95% CI: 1.15–3.32).ConclusionMore than one-third of the households in the study area dropped out of the CBHI scheme. This study identified several factors that are significantly associated with the CBHI dropout rate. These factors include family size, age of the household head, educational level, type of membership, absence of chronic illness in the household, experiences of leaving health facilities without treatment, and lack of adequate laboratory services. Therefore, we strongly recommend that the government and relevant stakeholders take action to address these factors in order to reduce dropout rates and improve the sustainability of the scheme.